An Overview of the Characteristics and Potential of Calotropis procera From Botanical, Ecological, and Economic Perspectives - Kaur, Amarpreet; Batish, Daizy R.; Kaur, Shalinder; Chauhan, Bhagirath S. (Frontiers in Plant Science, 2021)
Calotropis procera (Aiton) Dryand. (commonly known as the apple of sodom, calotrope, and giant milkweed) is an evergreen, perennial shrub of the family Apocynaceae, mainly found in arid and semi-arid regions. It is a multipurpose plant, which can be utilized for medicine, fodder, and fuel purposes, timber and fiber production, phytoremediation, and synthesis of nanoparticles. It has been widely used in traditional medicinal systems across North Africa, Middle East Asia, and South-East Asia. At present, it is being extensively explored for its potential pharmacological applications. Several reports also suggest its prospects in the food, textile, and paper industries. Besides, C. procera has also been acknowledged as an ornamental species. High pharmacological potential and socio-economic value have led to the pantropical introduction of the plant. Morpho-physiological adaptations and the ability to tolerate various abiotic stresses enabled its naturalization beyond the introduced areas. Now, it is recognized as an obnoxious environmental weed in several parts of the world. Its unnatural expansion has been witnessed in the regions of South America, the Caribbean Islands, Australia, the Hawaiian Islands, Mexico, Seychelles, and several Pacific Islands. In Australia, nearly 3.7 million hectares of drier areas, including rangelands and Savannahs, have been invaded by the plant. In this review, multiple aspects of C. procera have been discussed including its general characteristics, current and potential uses, and invasive tendencies. The objectives of this review are a) to compile the information available in the literature on C. procera, to make it accessible for future research, b) to enlist together its potential applications being investigated in different fields, and c) to acknowledge C. procera as an emerging invasive species of arid and semi-arid regions.